T-cell senescence accelerates angiotensin II-induced target organ damage. Issue 1 (30th January 2020) - Pan, Xiao-Xi; Wu, Fang; Chen, Xiao-Hui; Chen, Dong-Rui; Chen, Hong-Jin; Kong, Ling-Ran; Ruan, Cheng-Chao; Gao, Ping-Jin
Abstract: Aims: Aging is a risk factor for cardiovascular diseases and adaptive immunity has been implicated in angiotensin (Ang) II-induced target organ dysfunction. Herein, we sought to determine the role of T-cell senescence in Ang II-induced target organ impairment and to explore the underlying mechanisms. Methods and results: Flow cytometric analysis revealed that T cell derived from aged mice exhibited immunosenescence. Adoptive transfer of aged T cells to immunodeficient RAG1 KO mice accelerates Ang II-induced cardiovascular and renal fibrosis compared with young T-cell transfer. Aged T cells also promote inflammatory factor expression and superoxide production in these target organs. In vivo and in vitro studies revealed that Ang II promotes interferon-gamma (IFN-γ) production in the aged T cells comparing to young T cells. Importantly, transfer of senescent T cell that IFN-γ KO mitigates the impairment. Aged T-cell-conditioned medium stimulates inflammatory factor expression and oxidative stress in Ang II-treated renal epithelial cells compared with young T cells, and these effects of aged T-cell-conditioned medium are blunted after IFN-γ-neutralizing antibody pre-treatment. Conclusion: These results provide a significant insight into the contribution of senescent T cells to Ang II-induced cardiovascular dysfunction and provide an attractive possibility that targeting T cell specifically might be a potential strategy to treat elderly hypertensive patients with end-organ dysfunction. Graphical Abstract: